2018
DOI: 10.1111/myc.12773
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of a combination of fungal biomarkers for the diagnosis of invasive fungal disease in high‐risk haematology patients

Abstract: We prospectively evaluated a combination of fungal biomarkers in adult haematology patients with focus on their clinical utility at different time points during the course of infection. In total, 135 patients were monitored once to twice weekly for serum (1-3)-ß-d-glucan (BG), galactomannan (GM), bis-methyl-gliotoxin and urinary d-arabinitol/l-arabinitol ratio. In all, 13 cases with proven or probable invasive fungal disease (IFD) were identified. The sensitivity of BG and GM at the time of diagnosis (TOD) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…This test is the most extensively used in clinics, has been validated in clinical studies, and has been endorsed in microbiological criteria for diagnosis of IA in all published guidelines (25,93,94). In addition, the decrease in GM values also can be used to monitor the efficacy of a treatment (109).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…This test is the most extensively used in clinics, has been validated in clinical studies, and has been endorsed in microbiological criteria for diagnosis of IA in all published guidelines (25,93,94). In addition, the decrease in GM values also can be used to monitor the efficacy of a treatment (109).…”
Section: Figmentioning
confidence: 99%
“…Currently, there is not a single serological diagnosis which is 100% reliable for the diagnosis of IA (111,(148)(149)(150). A combination of diagnostic tests significantly increased the detection rate (109,148,(151)(152)(153). Importantly, the performance of molecular diagnostic assays is hampered by the lack of a gold standard for diagnosis in the case of possible or probable IPA and the inability of these tests to distinguish between the different stages of the disease, from colonization to chronic noninvasive infection to IPA, all of which can coexist in the patient at risk.…”
Section: Figmentioning
confidence: 99%
“…The additional component separation gained by combining UHPLC and QTOF‐MS increases the specificity and makes misidentification significantly less likely. Indeed, all studies that failed to identify bmGT in patient samples after the initial study by Vidal‐García et al used some form of liquid chromatography–mass spectrometry. Other alternative detection methods, such as a fluorescently labelled aptamer structure‐switching assay, have been developed using spiked samples, but have yet to be evaluated in human samples.…”
Section: Discussionmentioning
confidence: 99%
“…Vidal‐García et al found bmGT to have a better sensitivity in serum than GM. However, several other studies failed to replicate these results, both in an animal model of IPA and in samples from patients with IPA . Furthermore, results from a mouse model suggest different kinetics and sensitivities of GT and bmGT depending on the host's immune status, whereby bmGT was only detected in lungs from a chronic granulomatous disease model (CGD), but not in bronchoalveolar lavage fluid (BALf) or serum from mice with CGD, neutropenia or after steroid treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Examples of which include the use of galactomannan in the diagnosis of invasive aspergillosis and cryptoccocal antigen for diagnosis of cryptococcosis. (1→3)‐β‐ d ‐glucan (BDG), a component of several fungal cell walls, provides another surrogate marker for the diagnosis of IFIs . Since its first assay developed in Japan in 1985, BDG has been recommended to diagnose probable IFIs by the European Organization for Research and Treatment of Cancer, the Mycoses Study Group, the European Society of Clinical Microbiology and Infectious Diseases, the Infectious Diseases Society of America and the American Society for Microbiology …”
Section: (1→3)‐β‐d‐glucan As An Emerging Diagnostic Toolmentioning
confidence: 99%